Gambaran Pelaksanaan Discharge Planning di Ruang Perawatan Jantung - Oktarina, Yosi; Nurhusna, Nurhusna; Subandi, Andi (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
Coronary heart disease (CHD) patients are vulnerable to rehospitalization. One of the reasons for the high rehospitalization rate in CHD patients is the implementation of inadequate discharge planning. The aim of this research is to find out an overview of the implementation of discharge planning in the cardiac inpatient room. This research was a descriptive analytical research with a survey design. The sample in this study was patients with coronary heart disease. The sampling technique used was convenience sampling. The sample size in this study was 67 people. The research used a discharge planning implementation questionnaire. Data were analyzed using quantitative descriptives presented in the form of frequencies and percentages. The results showed that the implementation of discharge planning in the fair category was 35.82%, good 31,34%, poor 23,88%, and very good 8,96%. Therefore, it is hoped that the implementation of discharge planning in the room can be improved through the availability of operational procedural standards regarding the implementation of structured and planned discharge planning so that the implementation of discharge planning in the room becomes more optimal. Abstrak Pasien penyakit jantung koroner (PJK) rentan mengalami rehosipitalisasi. Tingginya angka rehospitalisasi pada pasien PJK salah satunya dipengaruhi oleh pelaksanaan discharge planning yang tidak adekuat. Tujuan dari penelitian ini yaitu untuk mengetahui gambaran pelaksanaan discharge planning di ruang perawatan jantung. Penelitian ini merupakan penelitian deskriptif analitik dengan desain survey. Sampel dalam penelitian ini yaitu pasien dengan penyakit jantung koroner. Teknik sampling yang digunakan yaitu convenience sampling. Besar sampel dalam penelitian ini yaitu 67 orang. Penelitian menggunakan kuesioner pelaksanaan discharge planning. Data dianalisis menggunakan deskriptif kuantitatif yang disajikan dalam bentuk frekuensi dan persentase. Hasil penelitian menunjukkan pelaksanaan discharge planning dalam kategori cukup sebesar 35,82%, baik 31,34%, kurang baik 23,88%, dan sangat baik 8,96%. Oleh karena itu, diharapkan pelaksanaan discharge planning di ruangan tersebut dapat ditingkatkan melalui tersedianya standar prosedural operasional mengenai penerapan discharge planning yang terstruktur dan terencana sehingga pelaksanaan discharge planning di ruangan menjadi lebih optimal. Kata kunci: discharge planning, penyakit jantung koroner, rehospitalisasi